PERCEIVED EFFECTS OF AUTHENTIC, ETHICAL AND SERVANT LEADERSHIP STYLE ON ORGANISATIONAL COMMITMENT OF THE EMPLOYEES IN THE INFORMATION TECHNOLOGY SECTOR - Imtiaz Alam , Jugindar Singh Kartar Singh (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Pakistan has an emerging IT sector, which earns foreign exchange to the tune of $3.5 billion annually and employs over 300,000 IT experts. It is an evolving sector, which is experiencing high turnover ratio and lack of support from the top management, which reflects on low organisational commitment and inept leadership style. The purpose of this article is to accentuate the critical linkage between the perceived effectiveness of authentic, ethical and servant leadership styles towards the organisational commitment of the employees in the IT sector. The paper uses a review of the literature to examine the relationship of these relatively new leadership styles on organisational commitment. It highlights the mechanism through which these leadership styles influence employee’s organisational commitment as cited in the literature. This paper emphasizes that it is essential for executives to use an appropriate leadership style to enhance the organisational commitment of employees. The article also features that higher degree of organisational commitment decreases employee intention to leave. It also reveals a positive direct relationship between authentic, ethical and servant leadership styles and organisational commitment. The findings of the study elucidate the importance of organisational commitment and highlight the significance of an appropriate leadership style to enhance engagement and thereby, the performance of the organisation.